Використання соціологічних груп видів та методу "коктейлю" для класифікації лучної рослинності лісової та лісостепової зон рівнинної частини України - Куземко, А.А. (Український ботанічний журнал, 2012)
Представлены результаты применения социологических групп видов (СГВ) и метода «коктейля» для классификации растительности класса Molinio-Arrhenatheretea лесной и лесостепной зон равнинной части Украины. На основе анализа фитосоциологической базы данных, включающей 2 766 описаний травяной растительности, выделено 36 СГВ. 26 из них использованы для формулировки формальных определений 33 ассоциаций класса Molinio-Arrhenatheretea. Рассмотрены перспективы развития метода «коктейля» для решения различных проблем фитосоциологии, фитоэкологии и фитогеографии. The results of the use of the Cocktail method with sociological species groups for classification of the Molinio-Arrhenatheretea class vegetation in the Forest and Forest-Steppe zones of the plain part of Ukraine are presented. On the basis of phytosociological database consisting of 2766 relevés of the herbaceous vegetation 36 sociological species group were determined. 26 of them were used for formulating formal definitions of 33 associations of the MolinioArrhenatheretea class. The perspectives of the use of this method for solution of different problems in phytosociology, plant ecology, and phytogeography are considered.